Визначення раціональних параметрів забезпечення стійкості транспортних пакетів методами підвищення сил тертя між шарами тарних вантажів - Деренівська, Анастасія Василівна; Кривопляс-Володіна, Людмила Олександрівна; Токарчук, Сергій Володимирович (My University, 2020)
The problem of ensuring reliable sustainability and strength of transport packages is a priority in the system of end-to-end transportation of packaged items. The sustainability of the transport package depends on: the method of stacking packaged items on the pallet; physical and mechanical parameters of packing material and means of packing forming; methods and means of strapping the transport package; accuracy of operations of transport package making machine; strength of transport package and consumer packaging, that limits height the transport packages. The goal of the research was to determine the characteristic parameters that ensures the mutual movement of packaged items and ensure the sustainability of the transport package during loading and unloading transporting operations and storage operations. The subject of research was new packaging material, a cardboard flat for preventing slipping packed items, “Non-Slip Safety Grip for Palletsˮ. Tasks of the research — analysis of existing and selection of rational packaging technologies, development of the force loading scheme for transport package layers; determination of friction forces and inertial components for packed item layers during transporting operations; determination of the limit values of the friction coefficients, which arise between the packed item layers of and will ensure the stability of the transport package. Using this method of increasing the friction force between packaged item layers allows us to make a rationally choice to prevent the sliding of packaged item layers, to introduce a simplified scheme of the technological process, and to reduce the time of the kinematic cycle. There is no need to use different methods of stacking packaged item on the pallet and to spend time for using additional strapping material for the transport package. Проведене дослідження з використанням методу підвищення сил тертя між шарами тарних вантажів дає змогу визначити характерні параметри, які убезпечуватимуть взаємне переміщення тарних вантажів, забезпечуватимуть стійкість пакета за умови виконання навантажувально-розвантажувальних транспортно-складських робіт, підібрати відповідний пакетувальний засіб, спростити схему технологічного процесу пакетування та зменшити час кінематичного циклу пакетоформувальної машини.Проведенное исследование с использованием метода повышения сил трения между слоями тарных грузов позволяет определить характерные параметры, которые будут предупреждать взаимное перемещение тарных грузов, обеспечивать устойчивость пакета при условии выполнения погрузочно-разгрузочных транспортно-складских работ, выбрать соответствующее средство пакетирования, упростить схему технологического процесса пакетирования и уменьшить время кинематического цикла пакетоформирующей машины.
Keywords: пакетування; транспортна упаковка; пакетоформувальні машини; засоби скріплення; стійкість; шар; пакетирование; транспортная упаковка; пакетоформирующая машина; средства крепления; устойчивость; слой; transport package; transport package making machine; strapping means; sustainability; layer; кафедра мехатроніки та пакувальної техніки